Educational Innovation Of Salaf Pesantren In The Review Of Social Philosophy In Changing Social Life - Nurmahmudah, (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
Salaf pesantren play a significant role in Indonesia's Islamic education, promoting scientific progress and character development. To adapt to the changing needs of society, these pesantren have undertaken renewal efforts. This paper examines the educational innovations of Hidayatut Thullab pesantren from a social philosophy perspective, exploring how they influence social interactions within the pesantren community and society as a whole. The study uses a combination of literature and field research, employing domain analysis, component analysis, taxonomy analysis, and cultural theme analysis to understand the social dynamics involved. The findings reveal that this semi-modern salaf pesantren effectively builds a strong social culture through a well-structured curriculum, comprehensive Islamic teachings, and a community life rooted in salaf traditions. This creates a close-knit community with a strong Islamic identity, rich cultural values, and deep respect for the Kiai. However, the innovations are mainly limited to digitalizing da'wah communication through online mass media. While this has positively impacted religious outreach, its influence remains within a limited network, lacking wider national reach. This is partly due to the digital content not being unique enough to achieve viral popularity. Additionally, the pesantren's relationship with the surrounding community is not fully optimized. It remains confined to a traditional salaf system, limiting broader social engagement. As a result, its social influence is more restricted compared to modern pesantren. Unlike modern pesantren, this salaf pesantren faces challenges such as limited collaboration with the government and NGOs. This results in fewer integrated activities, inadequate facilities, and insufficient teacher support. Consequently, its development is more constrained compared to modern pesantren. To maximize its impact, the pesantren needs to adopt more innovative approaches, strengthen community relations, and expand collaborations to enhance educational quality and social influence.